2021
DOI: 10.1038/s42255-020-00323-1
|View full text |Cite
|
Sign up to set email alerts
|

Space-time logic of liver gene expression at sub-lobular scale

Abstract: The mammalian liver is a central hub for systemic metabolic homeostasis. Liver tissue is spatially structured, with hepatocytes operating in repeating lobules, and sub-lobule zones performing distinct functions. The liver is also subject to extensive temporal regulation, orchestrated by the interplay of the circadian clock, systemic signals and feeding rhythms. However, liver zonation was previously analyzed as a static phenomenon, and liver chronobiology at tissue level resolution. Here, we use single-cell RN… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
116
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(131 citation statements)
references
References 70 publications
10
116
0
Order By: Relevance
“…Cluster 1 expresses lactoylglutathione lyase ( GLO ), which is involved in the detoxification of a toxic bi-product of glycolysis, methylglyoxal (MG) [ 34 ], suggesting that the glycolysis pathway could be active in these cells. Furthermore, recent a publication also using scRNA-seq has demonstrated that pericentral hepatocytes express a large number of ribosomal related mRNAs [ 35 ], which was also found for cluster 1. In cluster 10, we find increased HILPDA expression, which is involved in regulating lipid droplet formation and triglyceride storage in hypoxic conditions [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 87%
“…Cluster 1 expresses lactoylglutathione lyase ( GLO ), which is involved in the detoxification of a toxic bi-product of glycolysis, methylglyoxal (MG) [ 34 ], suggesting that the glycolysis pathway could be active in these cells. Furthermore, recent a publication also using scRNA-seq has demonstrated that pericentral hepatocytes express a large number of ribosomal related mRNAs [ 35 ], which was also found for cluster 1. In cluster 10, we find increased HILPDA expression, which is involved in regulating lipid droplet formation and triglyceride storage in hypoxic conditions [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 87%
“…Our experimental data included hepatocytes from two mice sacrificed at 48 hours and two mice at 72 hours after APAP injection, dissociated using Liberase enzyme. In order to include control non-injected hepatocytes, hepatocytes from a previously published study (Droin et al, 2021) were integrated. Notably, the animals were held at the same facility prior to experiment as animals used for our experiments and cells isolation and library construction were performed similarly to the APAP experiments.…”
Section: Hepatocyte Processingmentioning
confidence: 99%
“…Fatsq files of these two mice were re-aligned and preprocessed as detailed above for our sequencing runs, to eliminate any bioinformatics biases. Individual Seurat objects were created for the two mice, filtering out cells with less than 1,000 total UMI count and with mitochondrial percentage of less than 9% and more than 35%, as was found to capture viable hepatocytes (Droin et al, 2021). These included 923 cells for ZT6A and 1,076 cells for ZT6B.…”
Section: Hepatocyte Processingmentioning
confidence: 99%
“…It synchronizes peripheral clocks through various neuronal, physiological, and hormonal signals (Bass et Takahashi, 2010; Green et al, 2008; Mohawk et al, 2012). However, tissues outside the suprachiasmatic nucleus contain local clocks and food intake acts as a synchronizing cue for peripheral clocks such as the liver clock (Koronowski et al, 2019) which is particularly sensitive to feeding (Damiola et al, 2000; Droin et al, 2021; Greenwell et al, 2019; Saini et al, 2013; Stokkan et al, 2001; Vollmers et al, 2009; Weger et al, 2021). Insulin production by pancreatic β-cells is under the control of a circadian clock and responsive to feeding (Perelis et al, 2016).…”
Section: Introductionmentioning
confidence: 99%